2020
DOI: 10.1097/mao.0000000000002452
|View full text |Cite
|
Sign up to set email alerts
|

Sound Measurement in Patient-Specific 3D Printed Bench Models of Venous Pulsatile Tinnitus

Abstract: Hypothesis:We hypothesize patient-specific flow models to be an adequate in vitro surrogate to allow for characterization of Pulsatile Tinnitus that affects 3-5 million Americans.Background: Pulsatile tinnitus (PT), rhythmic sounds without an extracorporeal source that patients appreciate, can be caused by aberrant blood flow in large cerebral veins near the cochlea. In order to investigate the sound production mechanism, we created 3D printed flow models based on patient-specific cerebral venous anatomies.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The blood flow sound of venous PT was previously studied using 3D-printed models via different recording methods. (13,15) In congruence with a recent in vitro study conducted by Valluru et al that found that the main power of PT fell below 600 Hz using an electrical stethoscope, (15) both our in vivo ultrasonography and in vitro experiments showed similar results regarding frequency components. However, since the properties of the materials used for 3D-printed models vary significantly among the studies, to avoid sound impedance and sound transmission loss caused by the applied materials, an intravascularly placed hydrophone allows the analysis of the magnitude of the flow amplitude generated inside the sigmoid sinus.…”
Section: Combining In Vitro Experimental Outcomes and In Vivo Detection Of The Fluid-borne Soundsupporting
confidence: 90%
“…The blood flow sound of venous PT was previously studied using 3D-printed models via different recording methods. (13,15) In congruence with a recent in vitro study conducted by Valluru et al that found that the main power of PT fell below 600 Hz using an electrical stethoscope, (15) both our in vivo ultrasonography and in vitro experiments showed similar results regarding frequency components. However, since the properties of the materials used for 3D-printed models vary significantly among the studies, to avoid sound impedance and sound transmission loss caused by the applied materials, an intravascularly placed hydrophone allows the analysis of the magnitude of the flow amplitude generated inside the sigmoid sinus.…”
Section: Combining In Vitro Experimental Outcomes and In Vivo Detection Of The Fluid-borne Soundsupporting
confidence: 90%
“…Development of patient-specific three-dimensional-printed flow models that mimic a patient's hemodynamic conditions also allows physicians to better narrow down the specific causes of a patient's PT, and simulate treatment before the intervention. 47 In the future, phase-contrast MRI (ie, four-dimensional flow), fluid dynamic modeling with sound simulation, and intravascular sound recordings will likely play a larger role in disease assessment, particularly as part of clinical trials. Arterial causes of PT, such as carotid stenosis and dAVF, can bear a risk of stroke in addition to causing PT, and therefore may warrant treatment for multiple reasons.…”
Section: Non-operative Treatment Of Tinnitusmentioning
confidence: 99%
“…We have provided our UCSF Cerebral Venous Disorder Testing form as online supplemental material, which guides our assessment of venous causes of PT currently. Development of patient-specific three-dimensional-printed flow models that mimic a patient’s hemodynamic conditions also allows physicians to better narrow down the specific causes of a patient’s PT, and simulate treatment before the intervention 47. In the future, phase-contrast MRI (ie, four-dimensional flow), fluid dynamic modeling with sound simulation, and intravascular sound recordings will likely play a larger role in disease assessment, particularly as part of clinical trials.…”
Section: Future Perspectivementioning
confidence: 99%
“…Extrinsic sensing applications to assess the sound transmission of PT inside the mastoid bone have recently been attempted on both in vivo and in vitro 3D-printing platforms ( Tian et al, 2019 ; Valluru et al, 2020 ; Hsieh and Wang, 2021 ). As the sound wave pressure dampens due to surrounding human anatomical structures, the acquisition of the absolute amplitude of PT in vivo can be rather arduous.…”
Section: Introductionmentioning
confidence: 99%